Enhancing Employee Performance in Sindh's HigherEducation Institutes: The Role of Commitment,Involvement and Appraisal (Journal of Asian Development Studies, 2024)
Enhancing employee performance involves setting clear expectations and providing continuousfeedback. It is essential to create a positive workplace. This study creates the necessity ofperformance appraisal activities to improve employee performance and achieve organizationalgoals. It investigates the impact of performance appraisal on employee performance in HigherEducation Institutions (HEIs) in Sindh, Pakistan. Structural Equation Modeling (SEM) wasemployed using SmartPLS to analyze the relationships between variables. It includes PerformanceAppraisal, Organizational Commitment, Job Involvement, and Employee Performance. A sampleof 127 participants was selected from various HEIs in Sindh, Pakistan. The findings reveal asignificant mediating effect of organizational commitment and job involvement on the relationshipbetween performance appraisal and employee performance. On the other hand, effectiveperformance appraisals enhance employee performance when supported by strong organizationalcommitment and job involvement. It includes recommendations that hold valuable knowledge andimplications for executive bodies and policymakers of HEIs.